A time series analysis of students enrolled in Italian universities from 2000 to 2021 - Minerva, Tommaso; De Santis, Annamaria; Bellini , Claudia; Sannicandro , Katia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2022)
In the last 20 years, the Italian university system has undergone various transformations. Two reforms (1999 and 2010) redesigned its educational offerings and governance system structure. These were superimposed by severe financial crises (2008, 2012, and 2020 with the pandemic from COVID-19) that eroded the pur-chasing power of families. Since 2005, 11 online universities (“università telematiche” in Italian) have been accredited. These phenomena have affected access to higher education and changed student enrollment flows to various universities. In this paper, we investigate university enrollment trends and mobility over the period 2000-2021, also concerning students’ residence, the type of university chosen, and the geographical location of institutions.